The Characterization and Phylogenetic Implications of the Mitochondrial Genomes of Antheminia varicornis and Carpocoris purpureipennis (Hemiptera: Pentatomidae) - Ying Wang; Ruijuan Yang; Xiuxiu Zhu; Chenguang Zheng; Wenjun Bu (Diversity, 2023)
The mitochondrial genome (mitogenome) has been widely used for structural comparisons and phylogenetic analyses of Hemiptera groups at different taxonomic levels. However, little is known about the mitogenomic characteristics of species from Antheminia and Carpocoris, two morphologically similar genera in the Pentatomidae family, and their phylogenetic relationships need to be further confirmed. In this study, the mitogenomes of Antheminia varicornis (Jakovlev, 1874) and Carpocoris purpureipennis (De Geer, 1773) were sequenced and analyzed. Coupled with previously published mitogenomes of Pentatomidae, we performed a phylogenetic analysis. The mitogenomes of A. varicornis and C. purpureipennis are conserved in terms of genomic structure, base composition, codon usage, and tRNA secondary structure. Each mitogenome contains the typical 37 genes and a control region and all genes are arranged in the same order as in the ancestral insect mitogenome. Nucleotide composition is highly biased with the third codon in PCGs displaying the highest A + T content. Phylogenetic analysis strongly supports the sister relationship between A. varicornis and C. purpureipennis. The phylogenetic trees show a strong support for the monophyly of Asopinae and Phyllocephalinae, while the monophyly of Pentatominae and Podopinae was rejected. Our study enriches the mitochondrial genome database of the genera Antheminia and Carpocoris and provides a valuable resource for further phylogenetic and evolutionary analyses of the Pentatomidae.